Supervisor Roles for the Doctoral Student’s Development into Independent Researcher - Tamoliūnė, Giedrė; Teresevičienė, Margarita (Pedagogika, 2017)
Doctoral education is one of the primary resources for the development and implementation of new knowledge and innovation across the Europe. Therefore, the implementation of doctoral studies and preparation and training of junior academics and researchers are seen as one of the main aims and missions of the University. Doctoral studies differ from other study levels in principle as they accentuate students’ distinguished autonomy and independency when the scientific supervisor is mentor and assistant more than a knowledge provider and student is taking more responsibility to become an independent researcher. This article presents short theoretical overview of different roles of scientific supervisor and results of in-depth interviews with doctoral students that reveal experiences of collaboration with supervisors as well as their roles that appear during the doctoral study process. Research results revealed that when collaborating with doctoral students, supervisors get involved mainly in activities that are directly related to preparation of doctoral thesis, i.e. provide consultations on research topic development, encourage students to be critical about their own work and search for new insights or perspectives, and generate new ideas together with doctoral student. However, according to the research results, supervisor’s roles in other organisational issues are less relevant, especially when talking about enculturation, where supervisor is expected to help doctoral student to integrate into local and public academic society, join international associations or research groups or have consultations with experts from the research field.